Climate‐Modulated Nutrient Conditions Along the Labrador Shelf: Evidence From Nitrogen Isotopes in a Six‐Hundred‐Year‐Old Crustose Coralline Alga. Issue 5 (3rd May 2021) - Doherty, John M.; Williams, Branwen; Kline, Esme; Adey, Walter; Thibodeau, Benoit
Abstract: The impacts of climate change on north Atlantic nutrient chemistry remain poorly understood, as there exist a multitude of rapidly changing biological and physical drivers of nutrient conditions throughout the region. Here, we present nitrogen isotope measurements derived from a six‐hundred‐year‐old crustose coralline alga (δ 15 Nalgal ) to elucidate historical and contemporary trends in nitrate utilization and circulation patterns along the Labrador Shelf. Prior to the early 1900s, we argue that intervals during which utilization approached completion were controlled by reduced nitrate advection linked to an increased proportion of nitrate‐poor polar waters and subdued Atlantic influence, as expected from concurrent negative modes of the Atlantic multidecadal oscillation. While nitrate conditions should have recovered in recent years, our record suggests that high utilization persisted since ∼1870, which we also attribute to reduced Atlantic advection, likely associated with the twentieth‐century anthropogenic weakening of the Atlantic meridional overturning circulation. These results highlight the role of ongoing climate‐induced circulation changes in modulating nutrient distributions throughout the subpolar north Atlantic, which may have implications for other environmental phenomena such as fisheries and oceanic carbon storage. Plain Language Summary: In the North Atlantic, nitrate is a key nutrient involved in regulating phytoplankton populations and is therefore also important for marine ecosystem dynamics and, potentially, oceanic carbon storage. Along the Labrador Shelf, near‐surface nitrate may be supplied by mixing from deeper waters or from its advection from relatively nitrate‐rich Atlantic waters via the Labrador Current. Previous work has suggested that the Labrador Current has weakened over the last century in concert with the reduction of larger‐scale oceanic circulation, likely due to anthropogenic climate change. Thus, it is not clear if the supply of nutrients to the Labrador Shelf has also been affected by industrial‐era changes to the Labrador Current. Here, we use high‐resolution geochemical paleo‐proxy data from a 600‐year‐old crustose coralline alga to reconstruct circulation patterns and nutrient conditions along the Labrador Shelf. Prior to ~1870, we find a significant association between negative modes of the Atlantic Multidecadal Oscillation (AMO; or, perhaps more appropriately, "Atlantic Multidecadal Variability") and reduced nitrate supply, which we argue is linked to an increased dominance of low‐nitrate polar waters comprising the Labrador Current's coastal inflow. However, we also find an anomalously prolonged interval of polar‐dominated waters and nearly complete nitrate consumption beginning at the onset of the industrial era, which we hypothesize is linked to the anthropogenic weakening of North Atlantic circulation. Key Points: Nitrogen isotopes from a crustose coralline alga are argued to record ocean circulation and nutrient utilization along the Labrador Shelf Past periods of increased polar inflow waters and nutrient utilization are linked to negative modes of the Atlantic multidecadal oscillation An anomalously long phase of low nutrient input since ∼1870 is linked to the weakening of the Atlantic meridional overturning circulation